Sustained Release of Lidocaine from Solvent-Free Biodegradable Poly[(d,l)-Lactide-co-Glycolide] (PLGA): In Vitro and In Vivo Study - Yi-Chuan Kau (Materials, 2014)
Local anesthetics are commonly used for pain relief by regional nerve blocking. In this study, we fabricated solvent-free biodegradable pellets to extend the duration of lidocaine release without any significant local or systemic toxicity levels. To manufacture the pellets, poly[(d,l)-lactide-co-glycolide] (PLGA) was first pre-mixed with lidocaine powder into different ratios. The powder mixture was then compressed with a mold (diameter of 1, 5, 8 or 10 mm) and sintered at 65 °C to form pellets. The in vitro release study showed that the lidocaine/PLGA pellets exhibited a tri-phase release behavior (a burst, a diffusion-controlled release and a degradation-dominated release) and reached completion around day 28. Scanning electron microscope (SEM) photos show that small channels could be found on the surfaces of the pellets on day 2. Furthermore, the polymer matrix swelled and fell apart on day 7, while the pellets became viscous after 10 days of in vitro elution. Perineural administration of the lidocaine/PLGA pellets produced anti-hypersensitivity effects lasting for at least 24 h in rats, significant when compared to the control group (a pure PLGA was pellet administered). In addition, no inflammation was detected within the nerve and in the neighboring muscle by histopathology.